Hearing, touching, and multisensory integration during mate choice - Lenschow, Constanze; Mendes, Ana Rita P.; Lima, Susana Q. (Frontiers in Neural Circuits, 2022)
Mate choice is a potent generator of diversity and a fundamental pillar for sexual selection and evolution. Mate choice is a multistage affair, where complex sensory information and elaborate actions are used to identify, scrutinize and evaluate potential mating partners. While widely accepted that communication during mate assessment relies on multimodal cues, most studies investigating the mechanisms controlling this fundamental behavior have restricted their focus to the dominant sensory modality used by the species under examination, such as vision in humans and smell in rodents. However, despite their undeniable importance for the initial recognition, attraction and approach towards a potential mate, other modalities gain relevance as the interaction progresses, amongst which are touch and audition. In this review we will (1) focus on recent findings of how touch and audition can contribute to the evaluation and choice of mating partners, (2) outline our current knowledge regarding the neuronal circuits processing touch and audition (amongst others) in the context of mate choice and ask (3) how these neural circuits are connected to areas that have been studied in the light of multisensory integration.